Society of Gastrointestinal Endoscopy of India Consensus Guidelines on Endoscopic Ultrasound-Guided Biliary Drainage: Part II (Technical Aspects) - Samanta, Jayanta; Udawat, Priyanka; Chowdhary, Sudipta Dhar; Gunjan, Deepak; Rai, Praveer; Bhatia, Vikram; Singla, Vikas; Mukewar, Saurabh; Mehta, Nilay; Achanta, Chalapathi Rao; Dalal, Ankit; Sahu, Manoj Kumar; Balekuduru, Avinash; Bale, Abhijit; Basha, Jahangir; Philip, Mathew; Rana, Surinder; Puri, Rajesh; Lakhtakia, Sundeep; Dhir, Vinay; India EUS Club (Journal of Digestive Endoscopy, 2023)
Endoscopic management of bile duct obstruction is a key aspect in gastroenterology practice and has evolved since the first description of biliary cannulation by McCune et al in 1968. Over many decades, the techniques and accessories have been refined, and currently, the first-line management for extrahepatic biliary obstruction is endoscopic retrograde cholangiopancreatography (ERCP). However, even in expert hands, the success rate of ERCP reaches up to 95%. In almost 4 to 16% cases, failure to cannulate the bile duct may necessitate other alternatives such as surgical bypass or, more commonly, percutaneous transhepatic biliary drainage (PTBD). While surgery is associated with high morbidity and mortality, PTBD has a very high reintervention and complication rate (∼80%) and poor quality of life. Almost parallelly, endoscopic ultrasound (EUS) has come a long way from a mere diagnostic tool to a substantial therapeutic option in various pancreaticobiliary diseases. Biliary drainage using EUS-guidance (EUS-BD) has gained momentum since the first report published by Giovannini et al in 2001. The concept of accessing the bile duct through a different route than the papilla, circumventing the shortcomings of PTBD, and sometimes bypassing the actual obstruction have enthused a lot of interest in this novel strategy. The three key methods of EUS-BD entail transluminal, antegrade, and rendezvous approach. Over the past decade, with growing experience, EUS-BD has been found to be equivalent to ERCP or PTBD for malignant obstruction with better success rates. EUS-BD, however, is not devoid of adverse events and can carry fatal adverse events. However, neither the technique of EUS-BD nor the accessories and stents for EUS-BD have been standardized. Additionally, different countries and regions have different availability of the accessories, making generalizability a difficult task. Thus, technical aspects of this evolving therapy need to be outlined. For these reasons, Society of Gastrointestinal Endoscopy of India (SGEI) deemed it appropriate to develop technical consensus statements for performing safe and successful EUS-BD.
Keywords: biliary drainage; endoscopic ultrasound; obstructive jaundice